Carol and John Steinbeck : Portrait of a Marriage - Shillinglaw, Susan (Book collections on Project MUSE., 2013)
Carol Henning Steinbeck, writer John Steinbeck's first wife, was his creative anchor, the inspiration for his great work of the 1930s, culminating in The Grapes of Wrath. Meeting at Lake Tahoe in 1928, their attachment was immediate, their personalities meshing in creative synergy. Carol was unconventional, artistic, and compelling. In the formative years of Steinbeck's career, living in San Francisco, Pacific Grove, Los Gatos, and Monterey, their Modernist circle included Ed Ricketts, Joseph Campbell, and Lincoln Steffens. In many ways, Carol's story is all too familiar: a creative and intelligent woman subsumes her own life and work into that of her husband. Together, they brought forth one of the enduring novels of the 20th century.